Maternal Outcomes in Pregnant Females at Term Having Low Amniotic Fluid Index - Sidra Iqbal; Umbreen Akram; Hira Shafqat; Muhammad Zeshan Ali; Muhammad Shoaib; Maria Arshad (Pakistan Journal of Health Sciences, 2026)
Low amniotic fluid index (AFI) at term is associated with increased obstetric intervention, but its relationship with maternal outcomes remains uncertain. Objectives: To assess maternal outcomes in term pregnancies with low AFI and evaluate their association with maternal age, BMI, parity, and previous cesarean section. Methods: This analytical cross-sectional study included 137 singleton term pregnancies with low AFI (0.050). Conclusions: In this analytical cross-sectional study, pregnancies with low AFI at term showed high rates of induction and cesarean delivery; however, maternal age, BMI, parity, and previous cesarean section were not significantly associated with adverse maternal outcomes within the study sample.